SIBLING RIVALRIES: Disputing Religious Missionary and House of Worship in Contemporary Indonesia - Qodir, Zuly (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
The issues of religious proselytization as well as the construction of house of worship are of main contentious topics inciting tensions between religious adherents, particularly between the minority Christians and the majority Muslims in contemporary Indonesia. This article discusses these two inter-religious problems and poses a question to extent that the competition between Muslim and Christians, both in their missionary activities and the building of new house of worship, inflicting inter-religious relation in contemporary Indonesia. Taken some cases as points of discussion, this article further offers that inclusive dialogue and social justice are solutions to minimize—even to prevent—the worsening tension between Muslim and Christians.